Nitrogen assimilation in Citrus based on CitEST data mining - Wickert,Ester (2007)
Assimilation of nitrate and ammonium are vital procedures for plant development and growth. From these primary paths of inorganic nitrogen assimilation, this metabolism integrates diverse paths for biosynthesis of macromolecules, such as amino acids and nucleotides, and the central intermediate metabolism, like carbon metabolism and photorespiration. This paper reports research performed in the CitEST (Citrus Expressed Sequence Tag) database for the main genes involved in nitrogen metabolism and those previously described in other organisms. The results show that a complete cluster of genes involved in the assimilation of nitrogen and the metabolisms of glutamine, glutamate, aspartate and asparagine can be found in the CitEST data. The main enzymes found were nitrate reductase (NR), nitrite reductase (NiR), glutamine synthetase (GS), glutamate synthetase (GOGAT), glutamate dehydrogenase (GDH), aspartate aminotransferase (AspAT) and asparagine synthetase (AS). The different enzymes involved in this metabolism have been shown to be highly conserved among the Citrus and Poncirus species. This work serves as a guide for future functional analysis of these enzymes in citrus.